The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1590/s0034-71081998000300009
|View full text |Cite
|
Sign up to set email alerts
|

Conteúdo estomacal dos tubarões azul (Prinace glauca) e anequim (Isurus oxyrinchus) em águas oceânicas no sul do Brasil

Abstract: Stomach content of blue sharks (Prinace glauca) and anequim (Isurus oxyrinchus) from oceanic waters of southern Brazil.Blue shark and shortfin mako shark are the main pelagic elasmobranchs species often captured on tuna longlining in Southern Brazil, during the second and third quarters of the year. A total of 68 stomachs of blue shark and 32 stomachs of shortfin mako shark were collected between August 1990 and June 1991.Results in the IRI (Index of Relative Importance) diagrams show that there is a better re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 1 publication
0
10
0
5
Order By: Relevance
“…As seen by the IRI 0.6%, this item may be even less important to individuals of A. superciliosus, in a way to corroborate data obtained by Preti et al (2008), who found such prey in only one stomach. As a common observation of objects originated by human activities and even so, found within the stomach contents of sharks, this one may also be an accidental fact such as this one shown by the crustaceans (Hazin et al 1994, Vaske-Júnior & Rincón-Filho 1998.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen by the IRI 0.6%, this item may be even less important to individuals of A. superciliosus, in a way to corroborate data obtained by Preti et al (2008), who found such prey in only one stomach. As a common observation of objects originated by human activities and even so, found within the stomach contents of sharks, this one may also be an accidental fact such as this one shown by the crustaceans (Hazin et al 1994, Vaske-Júnior & Rincón-Filho 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Lepidocybium flavobrunneum is a fish species whose individuals may grow to large sizes, as are some specimens caught by fishery equipments. According to Vaske-Júnior & Rincón-Filho (1998) some specimens, when caught by the fishery activities are frequently marked by bite marks caused by sharks. This may happen during the process of fishing and to the opportunistic behavior of these sharks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste caso, tais ocorrências parecem demonstrar o hábito oportunista dos tubarões, visto que vários estudos prévios apontam a ocorrência de objetos dessa natureza (Hazin et al 1994, Vaske-Jr. & Ríncon-Filho 1998, Simpfendorfer et al 2001, McCord & Campana 2003.…”
Section: Discussionunclassified
“…Devido a um eventual acúmulo de bicos nos estômagos oriundos de alimentação de horas ou de dias anteriores, não se pode determinar a quanto tempo o cefalópode foi predado e digerido (Vaske & Rincón, 1998).…”
Section: Methodsunclassified